The Role and Significance of Rates Relief for Supporting Businesses in Wales. (December 2014) - Peck, Frank; Parry, Simon; Mulvey, Gail; Jackson, Keith; Cabras, Ignazio; Jackson, Jacqui
This paper reports on a study which seeks to evaluate the role of small business rates relief as a means of government support for small businesses, in terms of both the financial benefit for recipient businesses and the symbolic significance of rates relief as a form of state support for the small business community in general. In doing so, the paper engages with the theoretical debate regarding the effectiveness and targeting of support to small businesses and how best to achieve this. The paper is based upon a survey of 391 small businesses receiving rates relief in Wales. The study contributes to the literature by filling a gap in our knowledge of business perception of the impact of rates relief and identifying some of the positive and negative aspects of such support mechanisms.